Sinergi Kepemimpinan Transformatif dan Etos Kerja Guru sebagai Determinan Hasil Belajar Siswa: Bukti Empirik pada Pendidikan Madrasah - Endah Winarti; Nena Dwi Astuti; Binti Nasukah (Jurnal Multidisiplin Ibrahimy, 2025)
This study aims to analyze the influence of transformational leadership style of madrasah principals and teachers' work ethic on students' learning outcomes. The research is grounded in the urgency of improving learning quality in madrasahs through the optimization of leadership roles and teacher professionalism. A quantitative associative approach was employed in this study. A purposive sample of 176 eighth-grade students from four madrasah tsanawiyah in Batu Ampar District, East Kalimantan, was selected. Data were collected through a validated and reliable Likert-scale questionnaire. Out of the total responses, 173 were returned in usable condition and analyzed using multiple linear regression. The results revealed that both transformational leadership and teachers' work ethic significantly influence students' learning outcomes, both partially and simultaneously. These findings emphasize the importance of inspirational leadership and a strong work ethic in fostering a conducive learning environment in madrasahs. The practical implication of this study encourages the development of principal leadership training and continuous teacher work ethic enhancement programs. Furthermore, this research enriches the literature on Islamic educational leadership and serves as a reference for policymaking in improving madrasah education quality.